Brand equity value: consumer based approach versus financial approach: a case study using a portuguese bank - Coutinho, Camila (2018)
This study aimed to determine the brand equity value (BEV, hereinafter) of the “Banco BPI” from the costumers and financial perspective, based on 250 surveys to BPI customers to determine the BEV in the customers’ perspective and the application of EVA method to determine the BEV in the financial perspective. Respondents showed a positive perception on the various dimensions of the perceived brand value. However, the dimension that had the highest average was the notoriety and the lowest was the overall evaluation of the brand. The BVE in the financial perspective was obtained by using EVA method via different possible scenarios for the growth of the invested capital and results and by comparison with the value of the company, using benchmark variables (of “Millenium BCP” bank, another Portuguese bank). Thus, positive results were obtained in both perspectives, concluding that the brand “Banco BPI” has an overall positive value.